Religiousness and Depressive Symptoms in Five Ethnic Adolescent Groups - LE, Thao N. (Institutional Knowledge at Singapore Management University, 2007)
This study examined the relation between religiousness and depressive symptoms in African American, Asian American, European American, Hispanic American, and Native American adolescents (N = 13,317) in the United States with self-esteem and school attachment as potential mediators in this link. The data were taken from a nationally represented sample of adolescents in Grades 7 through 12, from the National Longitudinal Study of Adolescent Health (Add Health). Structural equation analyses with measurement and structural invariance across the five ethnic groups and gender supported the model that religiousness, as a composite of internal and external religiousness items, negatively predicted depressive symptoms 1 year later controlling for baseline depressive symptoms. Self-esteem and school attachment partially mediated this link but only for European American and African American adolescents.